What might be an impact of emotional intelligence on pharmacy practice? - Senćanski, Dejan; Marinković, Valentina; Tadić, Ivana (Archives of Pharmacy, 2022)
Emotional intelligence (EI) represents a set of skills that may help in the appraisal, expression, and effective regulation of our own emotions and the emotions of others. Pharmacists’ ability to communicate positively and create bonds with patients may have an impact on patients’ health outcomes during the provision of pharmaceutical care. Despite evidence that supports the hypothesis that developing EI in healthcare professionals (HCPs) may increase their capacity to improve patients’ health-related outcomes, little is known about it in pharmacy practice. Our study aimed to critically appraise available data on the potential impact of EI on pharmacy practice. The search of papers in English published between 2000 and 2021 was performed in the PubMed, Web of Science, and Embase databases, by defined inclusion criteria. Only four papers were selected for further analysis. In the study on the pharmacy leadership programs, it was found that they may support the enhancement of EI levels. Another study suggested that hospital pharmacists’ EI may influence the reversal of the negative correlation between autistic-like traits and empathy. A positive correlation between EI and entrepreneurial orientation was found in a study that involved practicing community pharmacists. One of the studies emphasized pharmacists’ superiority among various HCPs in the social skills, self-motivation, and self-awareness EI sub-domains. Further research is required to provide evidence on the potential impact of EI and EI development programs on the pharmacy practice, and patients’ health-related outcomes. Such studies in Serbia would add strong value to the evolution of pharmaceutical care.